2021
DOI: 10.1007/s00402-021-03979-w
|View full text |Cite
|
Sign up to set email alerts
|

Patients with stage II of the knee osteoarthritis most likely benefit from the intra-articular injections of autologous adipose tissue—from 2 years of follow-up studies

Abstract: Background Knee osteoarthritis (OA) is a common, chronic, progressive and degenerative disease which affects patients’ quality of life and may cause disability and social isolation. OA is a huge economic burden for the patient and a large strain for the whole healthcare system. Articular cartilage has a small potential to repair, with progressively more clinicians emphasizing cellular therapy. Subcutaneous fat tissue in human body is a large reservoir of mesenchymal stem cells (MSCs) and is been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…More recently, the same authors published another controlled study conducted on elderly patients, treated with SVF, which demonstrated to be beneficial even in patients older than 80 years with grade II to IV OA 48 . Nevertheless, a recent work showed that patients with stage II Kellgren-Lawrence (K-L) knee OA were most likely to benefit from intra-articular injections of ADSCs compared to the patients with stage IV K-L 49 .…”
Section: Mesenchimal Stem Cells Option For Treatment and Available Li...mentioning
confidence: 99%
“…More recently, the same authors published another controlled study conducted on elderly patients, treated with SVF, which demonstrated to be beneficial even in patients older than 80 years with grade II to IV OA 48 . Nevertheless, a recent work showed that patients with stage II Kellgren-Lawrence (K-L) knee OA were most likely to benefit from intra-articular injections of ADSCs compared to the patients with stage IV K-L 49 .…”
Section: Mesenchimal Stem Cells Option For Treatment and Available Li...mentioning
confidence: 99%